2023
DOI: 10.7554/elife.82424
|View full text |Cite
|
Sign up to set email alerts
|

Position representations of moving objects align with real-time position in the early visual response

Abstract: When interacting with the dynamic world, the brain receives outdated sensory information, due to the time required for neural transmission and processing. In motion perception, the brain may overcome these fundamental delays through predictively encoding the position of moving objects using information from their past trajectories. In the present study, we evaluated this proposition using multivariate analysis of high temporal resolution electroencephalographic data. We tracked neural position representations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 84 publications
(121 reference statements)
4
15
0
Order By: Relevance
“…This, in itself, is non-trivial as smoothly moving stimuli do not evoke the well-defined onset/offset responses that have previously been leveraged to decode the position of ‘apparent motion’ stimuli 16,18 . The fact that we can map the position of smoothly moving objects via a bank of pre-trained static position representations indicates that the position-specific activity patterns evoked by static and dynamic stimuli overlap, at least partially (consistent with 17 ).…”
Section: Resultssupporting
confidence: 68%
“…This, in itself, is non-trivial as smoothly moving stimuli do not evoke the well-defined onset/offset responses that have previously been leveraged to decode the position of ‘apparent motion’ stimuli 16,18 . The fact that we can map the position of smoothly moving objects via a bank of pre-trained static position representations indicates that the position-specific activity patterns evoked by static and dynamic stimuli overlap, at least partially (consistent with 17 ).…”
Section: Resultssupporting
confidence: 68%
“…Arguably, the signal contamination stemming from preceding dots may also account for the observed differences between independent pattern estimators, with the sustained influence from preceding dots being more pronounced in the short-ISI pattern estimator blocks, where subsequent stimuli are temporally closer together compared to the long-ISI pattern estimator blocks. Critically, control analysis convincingly demonstrated that this above-chance classification could not be explained by systematic eye movements as the same analysis using the x, y coordinates measured by the eye tracker did not result in above-chance classification (e.g., Chota et al, 2023;Johnson et al, 2023).…”
Section: Within-block Decoding: Increasing the Interval Between Succe...mentioning
confidence: 78%
“…Mechanisms described in these models are likely to interact with other processes that exploit the spatiotemporal structure of sensory environments. These processes include adaptation (Solomon & Kohn, 2014;Vogels, 2016;Whitmire & Stanley, 2016), surround suppression (Carandini & Heeger, 2012), end-stopping (Rao & Ballard, 1999), as well as retinal circuit mechanisms that rapidly adjust to local luminance levels (Rieke & Rudd, 2009), environmental image structure (Hosoya et al, 2005), periodic stimulation patterns (Schwartz et al, 2007;Schwartz & Berry, 2008) and smooth motion (Berry et al, 1999;Johnson et al, 2023). Systematically investigating these interactions will likely uncover a host of novel predictive phenomena, including feedforward or inherited effects across the visual cortical hierarchy (e.g., Dhruv et al, 2011;Larsson et al, 2016).…”
Section: Consequences Of Cued Expectations On Erpsmentioning
confidence: 99%